PENGUATAN ETIKA KRISTEN MELALUI PENDIDIKAN AGAMA KRISTEN BERDASARKAN MIKHA 6:8 DALAM KEHIDUPAN GENERASI MUDA - Risma Yulius; Resvi Pama'tam; Apriliani Allo Rerung (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study aims to analyze the strengthening of Christian ethics among the younger generation through Christian Religious Education, grounded in the principles of Micah 6:8. Employing a qualitative method with a library research approach, the study utilizes the Bible, scholarly books, journal articles, and other relevant literature as data sources. Content analysis is used to identify, interpret, and synthesize concepts related to Christian ethics, Christian Religious Education, and the implementation of the values ​​found in Micah 6:8. The findings indicate that the values ​​of acting justly, loving faithfulness, and walking humbly before God constitute a foundation for Christian ethics that remains relevant in addressing the moral challenges faced by the younger generation in the digital era. Christian Religious Education plays a crucial role in internalizing these values ​​through instruction, role modeling, habituation, and collaboration among the family, school, and church. Consistent implementation of the values ​​from Micah 6:8 fosters a younger generation characterized by Christian values, integrity, responsibility, and social concern, while equipping them to serve as witnesses for Christ amidst the changing times.